Novel Genomic Variants, Atypical Phenotypes and Evidence of a Digenic/Oligogenic Contribution to Disorders/Differences of Sex Development in a Large North African Cohort - Zidoune, Housna; Ladjouze, Asmahane; Chellat-Rezgoune, Djalila; Boukri, Asma; Dib, Scheher Aman; Nouri, Nassim; Tebibel, Meryem; Sifi, Karima; Abadi, Noureddine; Satta, Dalila; Benelmadani, Yasmina; Bignon-Topalovic, Joelle; et al. (Frontiers in Genetics, 2022)
The majority of individuals with disorders/differences of sex development (DSD) do not have a genetic etiology. However, recently new genes causing DSD have been reported and using the unbiased approach of whole exome sequencing (WES) the diagnostic yield should be improving. Here, we performed WES on a large cohort of 125 individuals all of Algerian origin, who presented with a wide range of DSD phenotypes. Parental consanguinity was reported in 36% of individuals. The genetic etiology was established in 49.6% (62/125) individuals of the total cohort, which includes 42.2% (35/83) of 46,XY non-syndromic DSD and 69.2% (27/39) of 46,XY syndromic DSD. Variants in the AR, HSD17B3, NR5A1 and SRD5A2 genes were the most common causes of DSD. Other variants were identified in genes associated with congenital hypogonadotropic hypogonadism (CHH), including the CHD7 and PROKR2. 30 previously unreported pathogenic/likely pathogenic variants involving a total of 25 different genes were identified in 22.4% of the cohort. Remarkably 11.5% of the 46,XY DSD group carried variants classified as pathogenic/likely pathogenic variant in more than one gene known to cause DSD. The data indicates that variants in PLXNA3, a candidate CHH gene, is unlikely to be involved in CHH. The data also suggest that NR2F2 variants may cause 46,XY DSD.